SHARING-SESSION AND CLINIC STRATEGI MENYUSUN PROPOSAL PENELITIAN DOSEN PEMULA - Jusuf Blegur; Zuvyati Aryani Tlonaen (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The Beginner Lecturer Research Grant (PDP) is an opportunity for non-functional and functional lecturer to practice their writing, researching, and research skills and abilities. The evaluation results found that only 16.6% of internal study program lecturers had ever passed the PDP grant, so it was necessary to provide training and assistance to lecturers so that their proposals could be funded through the PDP scheme. The methods used are sharing-session, distributing strategy tips for preparing the PDP), training (participants compose a PDP proposal according to the template), clinic (participants are assisted to correct the results of their proposal preparation directly), and evaluation (participants' work is evaluated using instruments). The participants were 15 people, including eight permanent lecturers (53.3%) from the internal study program and seven lecturers (46.6%) from the external study program. As a result, the participants' knowledge and understanding increased, and the lecturers' skills in preparing proposals also improved. Training and assistance in preparing proposals must be a severe concern of fostering a culture of writing and researching on campus to compete with critical ideas through national schemes prepared by the government, private sector, and others.